2016
DOI: 10.1007/s40291-016-0238-8
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of a Pharmacogenomics Test for Statin-Induced Myopathy in Cardiovascular High-Risk Patients Initiating a Statin

Abstract: BackgroundStatins are the mainstay hypercholesterolemia treatment and reduce the risk of cardiovascular events in patients. However, statin therapy is often interrupted in patients experiencing musculoskeletal pain or myopathy, which are common in this patient group. Currently, the standard tests for diagnosing statin myopathies are difficult to interpret. A pharmacogenomics (PGx) test to diagnose statin-induced myopathy would be highly desirable.MethodsWe developed a Markov state model to assess the cost-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…This was addressed by a study that examined the economic feasibility of a theoretical pharmacogenomic test for SI secondary to myopathy in high-risk populations, compared to the alternative of statin discontinuation. This study found that the use of a pharmacogenomic test is a beneficial strategy for any test costing less than CAN$356 (Canadian dollars) [35]. This was further supported by another study that found that in highrisk populations, using pharmacogenomic testing is also cost-effective to maintain patients on a statin given the cardiovascular benefit, despite possible risk of rhabdomyolysis [36].…”
Section: The Somatosensory Amplification Scale (Sas)mentioning
confidence: 60%
“…This was addressed by a study that examined the economic feasibility of a theoretical pharmacogenomic test for SI secondary to myopathy in high-risk populations, compared to the alternative of statin discontinuation. This study found that the use of a pharmacogenomic test is a beneficial strategy for any test costing less than CAN$356 (Canadian dollars) [35]. This was further supported by another study that found that in highrisk populations, using pharmacogenomic testing is also cost-effective to maintain patients on a statin given the cardiovascular benefit, despite possible risk of rhabdomyolysis [36].…”
Section: The Somatosensory Amplification Scale (Sas)mentioning
confidence: 60%
“…30 QALY utility weights from the literature were assigned to health states indicating CAD, 31 stroke, 31 and statin side effects. 31,32 Utility weights for high-risk individuals without CAD, stroke, or statin side effects accounted for utility decrement associated with age. 33…”
Section: Model Parametersmentioning
confidence: 99%
“…The pharmacogenomic properties of statins may guide to a personalized medicines with fewer risks and more efficiency. [4][5][6] RIGHT TIME…”
Section: Right Patientmentioning
confidence: 99%